2008
DOI: 10.2196/jmir.931
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of an Interactive Website to Support Long-Term Maintenance of Weight Loss

Abstract: Background For most individuals, long-term maintenance of weight loss requires long-term, supportive intervention. Internet-based weight loss maintenance programs offer considerable potential for meeting this need. Careful design processes are required to maximize adherence and minimize attrition.ObjectiveThis paper describes the development, implementation and use of a Web-based intervention program designed to help those who have recently lost weight sustain their weight loss over 1 year.MethodsThe weight lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(108 citation statements)
references
References 40 publications
2
104
1
1
Order By: Relevance
“…20 This has been supported by recent findings indicating that consistent self-monitoring of exercise is associated with greater total weight loss, greater amount of exercise, and fewer difficulties with exercise. [21][22][23][24] In moving past traditional methods of self-monitoring such as paper-and-pen diaries, research has found that technology can simplify the monitoring process. 25 This can include recording one's progress of food intake and physical activity using online journaling, handheld devices such as personal digital assistants (PDAs), and spreadsheets.…”
Section: Self-monitoringmentioning
confidence: 99%
“…20 This has been supported by recent findings indicating that consistent self-monitoring of exercise is associated with greater total weight loss, greater amount of exercise, and fewer difficulties with exercise. [21][22][23][24] In moving past traditional methods of self-monitoring such as paper-and-pen diaries, research has found that technology can simplify the monitoring process. 25 This can include recording one's progress of food intake and physical activity using online journaling, handheld devices such as personal digital assistants (PDAs), and spreadsheets.…”
Section: Self-monitoringmentioning
confidence: 99%
“…Authors either claim to have employed a userdriven design approach without engaging real users in their study (Currim et al, 2006;Stevens et al, 2008;Tang et al, 2003;Thursky & Mahemoff, 2007) or do not consider the factors affecting adoption (Boulos, 2006;Ferney & Marshall, 2006;Fetters, 2004;Keulers et al, 2006;Scandurra et al, 2008). …”
Section: Modelsmentioning
confidence: 99%
“…We feel that the approach taken here, examining one community over time, provides insights that the approach may have had an effect, as well as suggestions of a promising approach to be considered in other designs. This approach is similar to other longitudinal studies of website use (e.g., Lee, 2012;Leslie, Marshall, Owen, & Bauman, 2005;Stevens et al, 2008). To further develop the design approach in future work, we would create specific hypotheses about the effects of applying different types of design changes to the website, apply these changes incrementally, and carefully track the effects on website usage, website communications, and social network graphs.…”
Section: Website Communicationmentioning
confidence: 99%